Emergence of a new me: Experiences of women diagnosed with HER2-positive breast cancer. - Josianne Scerri; Janice Agius; Michael Galea (PLoS ONE)
Breast cancer subtypes vary in prevalence, prognosis, treatment protocols, and side-effect profiles, that may impact patients' lived experiences. Despite this, studies often group the experiences of persons with breast cancer together. The aim of this study was to explore the lived experiences of non-metastatic women diagnosed with Herceptin2-positive breast cancer, from diagnosis to the completion of treatment. Semi-structured interviews were conducted with 13 women who had undergone treatment for HER2 + breast cancer within the past two years. Their ages ranged between 32-79 years. Data collected were analysed using interpretative phenomenological analysis. Four experiential themes emerged: 'My world came crashing down,' 'The countdown,' 'To do or not to do, that is the question,' and 'Nearing the end of my journey.' These themes correspond to four phases of the participants' experiences: (i) the diagnostic phase, (ii) the neoadjuvant chemotherapy phase, (iii) the surgical phase, and (iv) the post-surgery adjuvant phase. The diagnosis elicited strong emotional reactions due the particularly aggressive nature of this type of cancer. However, the availability of targeted treatment and having a relatively common subtype of breast cancer provided hope for recovery. Throughout the neoadjuvant phase, participants experienced a range of emotions, including anxiety over missing any treatment, distress about changes in body-image, and concerns for their families. As treatment approached its end, they felt relieved but also anxious about the possibility of a recurrence. Understanding the narratives of women having Herceptin2-positive breast cancer, allows health professionals to better address their unique needs, concerns, and values, leading to the development of personalised care plans that target their lived experiences.